Changing Perceptions of Urban Retail Regulation: Sundays in the German City of Cologne - Jens K. Perret; Martin Fontanari (Urban Science)
Compared to multiple other European countries, Germany still lists among those countries restricting the operation of most retail activities on Sundays as well as public holidays. For a long time, the German populace backed this decision. The COVID-19 crisis had distinct effects on retail behavior, expectations, and perceptions among broad strata of German society. To quantify these changes, this study implements the results of two surveys from 2018 and 2025. Both samples were drawn from among the population of the fourth-largest German city of Cologne and visitors to the city. The results of t-tests and multiple multivariate regression analyses indicate that visitors still attend retail Sundays for hedonistic motives, i.e., related events, but in 2025 utilitarian motives have become more essential. While the amount of money spent during retail Sundays increased, this development is primarily driven by visitors not native to Cologne. However, city events continue to draw visitors and should be continued by city management. The financial potential for retailers by abolishing the German Shop Closing Act consequently remains limited, and its abolishment would only increase the ease of shoppers. Thus, legal changes to the act will have only limited potential for urban economic development.